Business Feasibility Study Analysis of Typical Madurese Souvenir Business in Burneh District Reviewed from Financial Aspects - Samsul Arifin; Abdur Rohman (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
In this current era, the economy in Indonesia is now very sophisticated and modern, a lot of effort is made by someone for their living, starting from snacks at every meal, so the production of typical Madurese souvenirs is carried out to develop the business. This research is a type of field research. This research was conducted on Jl. Raya Suramadu, Genangkah, Burneh, District. Burneh, Bangkalan Regency, East Java. The data sources used are primary data and secondary data, etc.: observations, interviews and documentation. The data analysis techniques applied in the exam refer to financial analysis, namely financial aspects using the provisions of Payback Period (PP), Net Present Value (NPV). ), Profitability Index (PI), and Internal Rate of Return (IRR). The results of the analysis of the feasibility study for the Madurese business from the financial aspect that we reviewed were results at a discount rate of 10%. With the feasibility study criteria, the business produces PP for 9 months with an NPV of IDR 269,653,859, with a PI value of 1.10% and a total IRR of 62%.